2019
DOI: 10.3390/ijerph16244958
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Health-Promotion Program Based on the Action Research Paradigm to Reduce Cardiovascular Disease Risk Factors among Blue Collar Workers

Abstract: This study developed and evaluated a health management program based on the participant-centered concept of action research to reduce cardiovascular disease (CVD) risk factors among blue collar workers. Data from structured questionnaires completed by 32 workers in a small-to-medium sized workplace from September 2015 to October 2016 as well as participants’ anthropometrical (weight and waist) and biological (blood pressure, glucose, total cholesterol, triglyceride, high-density lipoprotein (HDL), and low-dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…Lifestyle and integrated interventions, including exercise, nutrition and other components, may reduce the risk of CVD among workers [9,30]. In addition, the development of standardized interventions for objectively monitoring the risk of CVD among workers is identified as a potential benefit of researching lifestyle interventions for workers with known CVD risk factors, including systolic and diastolic blood pressure and BMI [22].…”
Section: Discussionmentioning
confidence: 99%
“…Lifestyle and integrated interventions, including exercise, nutrition and other components, may reduce the risk of CVD among workers [9,30]. In addition, the development of standardized interventions for objectively monitoring the risk of CVD among workers is identified as a potential benefit of researching lifestyle interventions for workers with known CVD risk factors, including systolic and diastolic blood pressure and BMI [22].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that the socioeconomic status of blue-collar workers in small-sized businesses is relatively lower than in white-collar workers, and that the groups in the higher socioeconomic status enjoyed better diet and health benefits than vulnerable groups with lower socioeconomic status, suggesting that the higher socioeconomic status group had less exposure to CVD risk [ 17 , 18 ]. In this study, however, the workers in small–medium-sized workplaces overlooked the importance of health management for themselves because their priority was on financial values rather than health management for CVD, due to their low income and family responsibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it is suggested to conduct additional research, which identifies contextual risk factors affecting CVD in small workplace workers at the extended community and policy levels. Third, previous study suggests that participant-centered intervention methodologies such as participatory action research (PAR) and Participatory Action-Oriented Training (PAOT) in the workplace as well as qualitative research method could be the effective health promotion programs to improve health-related self-regulation and health-promoting behavior for workers [ 18 ]. Therefore, additional PAR or PAOT intervention studies should be conducted to elucidate the effect of participant-centered methodologies on reducing CVD risk for workers in small–medium-sized workplaces.…”
Section: Discussionmentioning
confidence: 99%
“…The high-risk profile is correlated with indices of overweight/obesity (independently of other factors such as race, gender, and environment), with higher risk in overweight and obese individuals [2][3][4][5]. Therefore, evaluations of both anthropometric/body composition indices and the lipid panel are valuable tools in assessing risk for cardiovascular problems [6,7].…”
Section: Introductionmentioning
confidence: 99%